1995
DOI: 10.1088/0953-4075/28/12/012
|View full text |Cite
|
Sign up to set email alerts
|

High resolution threshold photoelectron spectroscopy of rare gas dimers

Abstract: Information on the structure of the ions of neon, argon, krypton and xenon dimers has been obtained using threshold photoelectron spectroscopy and synchrotron radiation under conditions of high resolution. Vibrational structure has been well resolved for the ground state of all these species thus allowing accurate values for the spectroscopic constants to be derived. Structure corresponding to excited states of the dimer ions dissociating to the 2P3/2,1/2 levels of the atomic ion have also been identified and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
3

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 28 publications
1
41
3
Order By: Relevance
“…In early theoretical work [12,13] it was concluded that this state is repulsive. More recent ab initio studies find a dissociation energy D 0 = 202 cm À1 [16] or 103 cm À1 [17], much smaller than the experimental value of %600 cm À1 [20,22].…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…In early theoretical work [12,13] it was concluded that this state is repulsive. More recent ab initio studies find a dissociation energy D 0 = 202 cm À1 [16] or 103 cm À1 [17], much smaller than the experimental value of %600 cm À1 [20,22].…”
Section: Introductionmentioning
confidence: 65%
“…1. Moreover, a rich body of experimental data has been obtained [18], most recently by high-resolution threshold photoelectron spectroscopy [4,[19][20][21][22][23][24]. There is good agreement between ab initio calculations and experimental data with one notable exception, the II(1/2g) state of Kr þ 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover it fulfils the condition E cr ≤ D 0 , where D 0 = (1.291 ± 0.010) eV [18] is the dissociation energy of the molecular ion Ne + 2 in its ground electronic state.…”
Section: Resultsmentioning
confidence: 92%
“…Spectroscopic fits to the microwave data are nevertheless possible for several slightly different quantum number assignments near dissociation. In the present work, this was resolved for the u states by including the e value of Kim et al 10 and the e x e value of Hall et al 9 in preliminary fits. This provided a number of possible vibrational assignments for the u-state levels for both ⍀ϭ1/2 and ⍀ϭ3/2.…”
Section: The Least-squares Fit Of the Interaction Potentialmentioning
confidence: 91%
“…Long-range states of neutral diatomic molecules are important in many contexts, including the photoassociation of laser-cooled atoms; 4 this is particularly topical because of the recent observation of photoassociation in a Bose-Einstein condensate, producing ultracold molecules in states near dissociation. 5 There have been a number of previous experimental investigations of the Ne 2 ϩ ion, principally in its ground electronic state, as listed in Table I 9 7.42 Ϯ0.16 cm Ϫ1 , is probably the more reliable because they observed many more vibrational levels.…”
Section: Introductionmentioning
confidence: 99%